Architectural Design of a Digital Maternal Health Monitoring System Based on the 2024 MCH Handbook: Documentation, Early Detection, and Pregnancy Danger Alarm Facilities - Nelli Roza; Muhammad Ropianto; Nurfitri (Postgraduate, University of Mataram, 2025)
Digital transformation in healthcare is a crucial strategy for improving the quality of maternal care in Indonesia, particularly in efforts to reduce the Maternal Mortality Rate (MMR). This study aims to design a digital system architecture for the 2024 MCH Handbook as a means of documentation, early detection, and alarm for pregnancy danger signs that is adaptive to island regions. The research method uses a descriptive qualitative approach with the Framework TOGAF (The Open Group Architecture Framework) as the basis for system design. Data were collected through digital literacy and accessibility questionnaires for pregnant women, in-depth interviews with health workers, as well as Focus Group Discussion (FGD) activities and expert validation from the fields of midwifery, public health, and information technology. The results showed that the digital literacy level of pregnant women was quite good in the information awareness dimension (52.38%), but still low in the information evaluation and application dimension. System accessibility was assessed as high (>50%) in terms of device availability and compatibility. Stakeholders expressed a strong need for a digital MCH Handbook system with danger alarm features, visit reminders, and a simple interface. The expert validation results obtained an average Aiken's V value of 0.88 (valid category), indicating that the system design is clinically, technically, and policy-wise feasible. The developed digital system architecture for the 2024 MCH Handbook is able to address field needs, support local innovations such as SMART ULING , and align with the national agenda for Digital Health Transformation . This system has the potential to be an effective solution to accelerate early detection of pregnancy risks, strengthen the integration of maternal services, and support efforts to reduce maternal mortality in island regions.